Pengembangan Media Pop Up Book CERDIK Terhadap Pencegahan Diabetes Melitus Tipe 2 Pada Kelas 6 (Anak SDN Kasomalang VI) - Fitriani, Riani (Jurnal Kesehatan Siliwangi, 2024)
The prevalence chronic kidney disease due to DM has increased to 8.5% or 853,240 million people. Referring to the high number of cases and management of DM, preventive measures are needed, one of which is education (health education), healthy living behavior (CERDIK) from an early age using the CERDIK Pop-Up Book media. Develop the CERDIK Pop-Up Book media for the prevention of diabetes mellitus in elementary school children which is suitable for use as a health education media. Method: research method uses research and development methods with the ADDIE approach. The total population is 20 grade 6 children at SDN Kasomalang VI. CERDIK Pop-Up Book media is A4 size and made from 260 gsm art paper. Obtained a score of 95.3% in the very good category from Material Experts, 100% in the very good category from Media Experts. There is an influence of using the CERDIK Pop-Up Book media with an increase of 60.34%. CERDIK Pop-Up Book media is A4 size, and made from 260 gsm art paper. The media was declared very good and very appropriate by the Expert and there was an influence of giving CERDIK Pop-Up Book media to 6th grade elementary school children.